Exploring the Addition of Herbal Residues on Fermentation Quality, Bacterial Communities, and Ruminal Greenhouse Gas Emissions of Paper Mulberry Silage - Li, Xiaomei; Chen, Fei; Xu, Jingjing; Guo, Linna; Xiong, Yi; Lin, Yanli; Ni, Kuikui; Yang, Fuyu (Frontiers in Microbiology, 2022)
This study aimed to investigate the influence of herbal residues on the fermentation quality and ruminal fermentation of paper mulberry silage. Clove, mint, and purple perilla residues were used as additives. Silage treatments were designed as control (no additives), 5% of clove, 5% of mint and 5% of purple perilla. After 21 and 75 days of fermentation, the fermentation characteristics, bacterial communities and ruminal greenhouse gas emissions in vitro incubation of paper mulberry were analyzed. The results showed that the employed herbal residues could reduce the protein losses in paper mulberry silage based on the lower contents of ammoniacal nitrogen and non-protein nitrogen. Compared with control, higher lactic acid and propionic acid contents were observed in the silages treated with mint and purple perilla, but with a higher acetic acid content in clove treatment. Real-time sequencing technology (SMRT) revealed that Lactobacillus was the dominant bacteria in all silages at the genus level, while the bacterial abundance in the treated silages differed greatly from control at the species level. Lactobacillus hammesii abundance was the highest in the control, while Lactobacillus acetotolerans was the first predominant in the treated silages. All the additives enhanced the digestibility of in vitro dry matter significantly. However, purple perilla decreased the production of total gas, methane and carbon dioxide. The above findings suggested that herbal residues have potential effects in improving fermentation quality, reducing protein loss, and modulating greenhouse gas emissions in rumen of paper mulberry silage by shifting bacterial community composition.